Selective aerobic oxidation of biomass-derived HMF to 2, 5-diformylfuran using a MOF-derived magnetic hollow Fe–Co nanocatalyst. Issue 10 (22nd February 2016) - Fang, Ruiqi; Luque, Rafael; Li, Yingwei
Abstract : The present work reports a sustainable, cost-effective, and highly efficient catalytic system for directly transforming HMF to DFF that afforded >99% DFF yield under relatively mild reaction conditions. Abstract : The conversion of renewable biomass resources into fuels, polymers, and fine chemicals provides solutions for the growing shortage of fossil resources, environmental pollution and a possible crisis in energy supply. 5-Hydroxymethylfurfural (HMF) is an important biomass-derived platform chemical, and its selective oxidation to multifunctional molecules such as 2, 5-diformylfuran (DFF) remains an ongoing challenge. The present work reports a sustainable, cost-effective, and highly efficient catalytic system for directly transforming HMF to DFF that afforded >99% DFF yield under relatively mild reaction conditions. The reaction was catalyzed by naturally abundant and non-noble Fe–Co based catalysts derived from a metal–organic framework (MIL-45b) employed as a sacrificial template. The unique hollow structure of the nanomaterial favored the adsorption of HMF and quick desorption of the formed DFF from the catalyst surface, leading to a high yield of DFF that could be comparable to that obtained with noble metal catalysts under similar conditions. The catalyst could also be easily recovered and reused up to six runs without any significant loss in reactivity.